Training on the Utilization of the HVSR Geophysical Method Based on the Concept of Mechanical Wave Propagation for Earthquake Hazard Potential Analysis in Kuto Rejo Village - Hadi, Arif Ismul; Refrizon; Muda Lubis, Ashar; Johan, Septi; Halauddin (UNIB Press, 2025)
Kepahiang Regency has a high potential for earthquake hazards. This is because the Kepahiang area is located in the subduction zone of the Indo-Australian tectonic plate movement in the ocean and the movement of the Musi segment of the Sumatra fault on land as the main fault. As an area with high earthquake hazard potential and its location near the Musi segment fault, efforts are needed to reduce the risk of disasters due to earthquakes through the activity